(untitled) (Literary Voice, 2024)
Statues within urban landscapes serve as powerful instruments shaping the collective ethos of communities and ethnic groups, functioning as identity markers and emblematic embodiments of power and ideology. Crafted as vehicles for political messaging throughout history, statues endure as relics, actively participating in societal discourse. They represent collective imprints, embodying a community’s history and broadcasting its traditions, institutions, beliefs, and ideologies. This study explores the commemorative practices and visual rhetoric of monuments and statues, focusing on the iconic status of Maharaja Ranjit Singh in Punjab. Analyzing statues in Amritsar and Ludhiana, it delves into their symbolic allure, guided by Mitchell’s Picture Theory, Roland Barthes’ conception of images as political subjects, and Stuart Hall’s “Encoding-Decoding” discourse. Unearthing the interplay of images in shaping collective memory, this research illuminates the contemporary political and cultural significance of Maharaja Ranjit Singh’s statues.